Students' Choices of University from Consumer Behavior Perspectives : A Case Study of UUM Undergraduate Students - Jamilah, Samsudin (2004)
This study explores the decision-making process of students in choosing a university for an undergraduate study and its relationship with the factors that influence the pursuit of higher education, motivation to search and perceive the criteria in choosing university. Respondents were randomly selected from among the first year undergraduate students at Universiti Utara Malaysia (UUM), the only university specializing in management programs in Malaysia. The theoretical framework of this study was modified from Brennan’ model (Brennan, 2001). The study found that the decision-making capability of students based on the uncertainty orientation where students actively seek information about higher learning institution face the risk of an ambiguity future. The study also found that students’ pursuit of higher education is much influenced by their peers. Their motivation to search a higher learning institution is mostly motivated by the purchasing decision involvement or their level of involvement and sense of importance about purchase decision. The findings also revealed that the top five criteria perceived by students in choosing a university are education facilities, job placement programs, degree program offered, safety on campus, and relevance of program to a chosen career. The findings of the study benefit the university especially the education marketers and also the policy makers in designing their effective marketing campaign and promotional activities to attract student to choose the university.